Parenting style in building learning motivation in children: A case study in migrant workers’ families in Indonesia - Ulvi Oktaliana; Maria Veronika Roesminingsih; Suhanadji Suhanadji (International Journal of Educational Studies in Social Sciences (IJESSS), 2021)
This study aims to describe the role of parenting to students whose parents work as immigrants with substance in the form of student opinions, as well as to describe the learning motivation of students whose parents work as migrant workers with several approaches related to learning motivation. The study used a qualitative approach that took data based on the results of interviews and direct observations as a data collection instrument and then carried out descriptive analysis. The sample of this study was conducted on students at MI Al-Khoiriyah and SDN Langenharjo 2 schools whose parents worked as immigrants. The results showed that students realized that with the parenting pattern of parents who worked as immigrants this situation was only temporary, their parents worked for money to be able to meet their needs at home and students' educational needs. However, in general, students feel sad when their parents are away from them for a long time so that students experience a lack of direct parental love. Therefore, in general, students whose parents work as immigrants do not show good or high learning motivation. This can be seen from the incompleteness of eight indicators of student learning motivation at school. Suggestions for further research in the future are also discussed.